2002
DOI: 10.1200/jco.2002.07.166
|View full text |Cite
|
Sign up to set email alerts
|

Low-Risk Persistent Gestational Trophoblastic Disease: Outcome After Initial Treatment With Low-Dose Methotrexate and Folinic Acid From 1992 to 2000

Abstract: Single-agent dactinomycin has activity in patients with low-risk GTD who develop MTX resistance and whose hCG is low. Simplifying the stratification of GTD into two classes (low- and high-risk) does not compromise overall outcome and may reduce the risk of second tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
181
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(195 citation statements)
references
References 19 publications
9
181
2
3
Order By: Relevance
“…Initial reports on 487 patients from Charing Cross (Bagshawe et al, 1989) and 115 from Sheffield (Dorreen et al, 1988) confirmed its efficacy, although it was noted that up to 30% of patients needed second-line treatment due to resistance or, less frequently, toxicity. In the recent Charing Cross report of use of this regimen for low-/intermediate-risk patients, 33.2% of 485 patients required a change in treatment; however, overall survival was 100% (McNeish et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial reports on 487 patients from Charing Cross (Bagshawe et al, 1989) and 115 from Sheffield (Dorreen et al, 1988) confirmed its efficacy, although it was noted that up to 30% of patients needed second-line treatment due to resistance or, less frequently, toxicity. In the recent Charing Cross report of use of this regimen for low-/intermediate-risk patients, 33.2% of 485 patients required a change in treatment; however, overall survival was 100% (McNeish et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There are several different protocols for treatment administration, but larger comparative studies of their efficacy and toxicity, as well as long-term outcome are needed. However, the UK experience with low-dose intramuscular methotrexate is extensive (Dorreen et al, 1988;Bagshawe et al, 1989;McNeish et al, 2002) and this is a relatively inexpensive and cost beneficial treatment (Hancock, 1997). Our study confirms the efficacy and relative lack of severe short-and long-term toxicity of this regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical, biochemical and radiological details (either computer tomography (CT) or chest X-ray (CXR), or both) at presentation and on completion of chemotherapy were recorded. At presentation for chemotherapy, patients were staged according to nationally and internationally accepted criteria for GTN, stratified into low-or high-risk groups, and treated accordingly (Bagshawe, 1976;Kohorn, 2001;McNeish et al, 2002). Individuals with low-risk disease were treated with subcutaneous methotrexate and folinic acid, whereas those with high-risk disease were given weekly combination chemotherapy, comprising of etoposide, methotrexate, and actinomycin alternating with cyclophospohmide and vincristine (EMA/CO).…”
Section: Methodsmentioning
confidence: 99%
“…If there is an inadequate response to the initial single agent, a significant elevation in hCG level, development of metastasis, or resistance to sequential single-agent chemotherapy, multi-agent chemotherapy as for high-risk disease should be initiated [2]. Studies in the UK showed that if the hCG level is less than 100 IU/L or 300 IU/L, change to single-agent Act-D gives a good response [2,28,29]; otherwise, multiple agents need to be used.…”
Section: Low-risk Gestational Trophoblastic Neoplasiamentioning
confidence: 99%